СУЩЕСТВУЕТ ЛИ МЕЙНСТРИМ В СОВРЕМЕННОЙ ЛИНГВИСТИКЕ? (Filološke pripombe, 2019)
The paper provides a critical survey of the current state of problems in modern linguistics. The article contents are disputed the problem of existence of paradigm in linguistics. The issue remains open.